The relationship between director’s compensation and audit fee: Empirical evidence from developing countries - Ardianto, Ardianto; Putri, Fiona Vista; Ghani, Nadzri Ab; Mardijuwono, Agus Widodo; Rochmah, Hidayati Nur; Soeprajitno, Roro Widya Ningtyas (International Journal of Management and Sustainability, 2023)
The present study investigates the correlation between director remuneration and audit fees within the context of a corporation operating in a developing nation. Additionally, this study investigates whether the extent of national consumption strengthens the association between director compensation and audit fees. This study employed the Ordinary Least Square (OLS) method to analyses a dataset consisting of 3,417 samples of non-financial firm data reported on the stock exchanges of Indonesia and Malaysia. The observation period for this study spanned from 2015 to 2019. The findings of this study indicate a substantial positive relationship between director salaries and audit fees in both countries. Furthermore, the evidence shows that the level of household consumption in a country will increase because of the positive relationship between director compensation and audit fees. In addition, CEOs and CFOs who have experience working as auditors carry a more negligible risk for the company. Meanwhile, directors' overcompensation will pose a greater risk for the company. This study is robust based on sensitivity testing using Coarsened Exact Matching (CEM) and Heckman regression. In general, the amount of compensation paid to the CEO shows the company's financial capacity, which reflects the company's liquidity and asset capabilities, which will be read as risk. Furthermore, the distinctiveness of the governance systems in these two countries, as observed in our sample, demonstrates a consistent outcome.